The role of microstructure in fatigue crack initiation of 9-12%Cr reduced activation ferritic-martensitic steel - Batista, Maria Natalia (2015)
Electron back-scattered diffraction together with scanning and transmission electron microscopy were used to study nucleation of microstructural fatigue cracks in reduced-activation ferritic-martensitic steel, EUROFER 97. Cylindrical specimens were cycled over different plastic-strain ranges in order to evaluate the evolution of the dislocation structure. Surface-damage evolution was studied in smooth notched specimens by an optical in situ system equipped with a high-resolution camera. In order to understand the crack-initiation mechanism, the dislocation microstructure that develops in the near-surface regions of the notch was compared with that of the bulk. The results demonstrate a strong influence of lath-martensite boundaries on fatigue-crack nucleation.